2003
DOI: 10.1046/j.1525-139x.2003.16093.x
|View full text |Cite
|
Sign up to set email alerts
|

RENAL RESEARCH INSTITUTE SYMPOSIUM: The Longitudinal Chronic Kidney Disease Study: A Prospective Cohort Study of Predialysis Renal Failure

Abstract: Chronic kidney disease (CKD) is a significant public health problem: every year the number of Americans living with CKD and requiring renal replacement therapy increases. In addition, individuals with CKD have substantially increased morbidity and mortality compared to the general population. The Longitudinal Chronic Kidney Dialysis (LCKD) Study is a multicenter, prospective, observational study of patients with moderate to severe CKD that was designed to better describe the course of the disease and the deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Although we did not detect a temporal pattern of increasing use of ACEi/ARBs within the relatively short timeframe of the administrative analysis, our literature review suggested a linear trend of increasing reported use of these medications among CKD patients over a broader observation period spanning 1990-2003 [31,33,39,42]. Concern for side effects may explain lack of administration to some CKD patients.…”
Section: Discussionmentioning
confidence: 55%
“…Although we did not detect a temporal pattern of increasing use of ACEi/ARBs within the relatively short timeframe of the administrative analysis, our literature review suggested a linear trend of increasing reported use of these medications among CKD patients over a broader observation period spanning 1990-2003 [31,33,39,42]. Concern for side effects may explain lack of administration to some CKD patients.…”
Section: Discussionmentioning
confidence: 55%
“…Data from all nephrology clinic visits were, therefore, recorded. Details of the study design have been previously published [10]. …”
Section: Methodsmentioning
confidence: 99%
“…The institutional review boards at all participating sites approved the study, and all patients provided written informed consent. Details of the study design have been published previously (10).…”
Section: Data Source: the Renal Research Institute Ckd Studymentioning
confidence: 99%